Description Of Knowledge and Attitudes of Monthly Injectable Contraceptive Users Regarding Acceptance and Compliance With the Booster Schedule - Ambarita, Bernadetta; Hutapea, Lely Maria; Sinabariba, Merlina; Sitepu, Aprilita Br (CV Putra Publisher, 2026)
Knowledge is the result of a person's understanding of a particular thing. Perception occurs through the five human senses, namely sight, hearing, smell, taste, and touch. Most human knowledge is obtained through the eyes and ears. 1-month injectable contraceptive injection has an important role in ensuring the effectiveness and sustainability of the use of this contraceptive method. This study aims to determine the description of knowledge and attitudes of 1-month injectable contraceptive acceptors with adherence to the repeat injection schedule at the Romauli Silalahi Clinic in 2025. This study is a descriptive study with an accidental sampling method by distributing questionnaires. The sample of this study was 30 respondents. Based on the results of this study, data was obtained that: knowledge of KB acceptors who were respondents was 30 people, the most knowledgeable was 15 people with a percentage of 50%, Attitude of 1-Month Injectable KB Acceptors at the Romauli Silalahi Clinic in 2025, it was found that most respondents had an attitude of agreement as many as 15 people (50%). Compliance of 1 Month KB Injection Acceptors at the Romauli Silalahi Clinic in 2025 was found that most respondents were in accordance with the repeat injection schedule, while 17 people (57%) were not on the repeat injection schedule. The description of mothers' knowledge about injectable contraception showed that 15 respondents (50%) had sufficient knowledge, 15 respondents (50%) agreed with injectable contraception every 1 month, and 17 respondents (57%) complied with injectable contraception every 1 month